Politics and Non/Partisanship: Is College Student Government a Neutral Space? (Higher Education Politics and Economics, 2022)
College student government is a notable form of student involvement in higher education, and one that has evolved over time. But student government is not without politics, from legislating on campus to making statements on local and even inter/national issues. This article illuminates data from a phenomenological study of nineteen former student government officers who ran for or served in post-college public office (e.g., mayors, city councilmembers, state senators, and more). Two major themes are rendered in this article: student government and non/partisanship and student government and decision-making power. Questions and recommendations are left as a way to better understand college students and student government, and exist as a calling to further interrogate this topic and form of student–and political–engagement.